Prenatal diagnosis of nail patella syndrome: A case report - Padmanabhan, L D; Yesodharan, D; Nampoothiri, S (Indian Journal of Radiology and Imaging, 2017)
The Nail Patella Syndrome (NPS) is an autosomal dominant connective tissue disorder affecting the nails, skeletal system, kidneys and eyes. Here, we report a case of NPS detected at 19 weeks of gestation. The movements of the elbow and knee joints were restricted and there was rotational deformity of the knee joints. To our knowledge, this is the first report of in-utero restriction of limb movements in a fetus with NPS.
Keywords: Limited extension of elbow and knee joints; nail patella syndrome; rotational defect of knee joint